A Novel Self‐Assembled Mitochondria‐Targeting Protein Nanoparticle Acting as Theranostic Platform for Cancer. Issue 2 (19th November 2018) - Zhu, Xin‐Jie; Li, Ri‐Fei; Xu, Liang; Yin, Hui; Chen, Long; Yuan, Ye; Zhong, Wu; Lin, Jian
Abstract: Self‐assembled protein nanoparticles have attracted much attention in biomedicine because of their biocompatibility and biodegradability. Protein nanoparticles have become widely utilized as diagnostic or therapeutic agents for various cancers. However, there are no reports that protein nanoparticles can specifically target mitochondria. This targeting is desirable, since mitochondria are critical in the development of cancer cells. In this study, the discovery of a novel self‐assembled metal protein nanoparticle, designated GST‐MT‐3, is reported, which targets the mitochondria of cancer cells within 30 min in vitro and rapidly accumulates in tumors within 1 h in vivo. The nanoparticles chelate cobalt ions [GST‐MT‐3(Co 2+ )], which induces reactive oxygen species (ROS) production and reduces the mitochondrial membrane potential. These effects lead to antitumor activity in vivo. GST‐MT‐3(Co 2+ ) with covalently conjugated paclitaxel synergistically suppress tumors and prolong survival. Importantly, the effective dosage of paclitaxel is 50‐fold lower than that utilized in standard chemotherapy (0.2 vs 10 mg kg −1 ). To the best of the authors' knowledge, GST‐MT‐3 is the first reported protein nanoparticle that targets mitochondria. It has the potential to be an excellent platform for combination therapies. Abstract : GST‐MT‐3(Co 2+ ) protein nanoparticles can accumulate in tumors within 1 h in vivo and target the mitochondria. Reactive oxygen species (ROS) production is induced via the release of cobalt ions. The mitochondrial membrane potential is reduced, resulting in cytotoxicity due to apoptosis of the cancer cells. GST‐MT‐3(Co 2+ ) protein nanoparticles in combination with paclitaxel act synergistically and enhance survival of mice.